Dampak Terapi Penerimaan dan Komitmen terhadap Harga Diri dan Ketakutan Melajang - Kristlyna, Eileen; Nanik, Nanik (Bulletin of Counseling and Psychotherapy, 2025)
Being single for some adult women who live in a society that has standards to get married soon will have negative impacts, such as receiving negative stigma, demands, and feelings of shame. These negative impacts can make single adult women have low self-esteem and high fear of being single. The hypothesis of this study is that acceptance and commitment therapy can increase self-esteem scores and decrease fear of being single scores in single adult women. This research using mixed method of quantitative & qualitative. The research design is a single case experimental design. Quantitative data were obtained using the Rosenberg self-esteem scale and the fear of being single scale. Qualitative data were obtained through observation and interviews of single experiences. Analysis of quantitative data using paired sample t-test & trend analysis, and qualitative data using descriptive description. The ACT intervention consists of 7 sessions, where each session lasts approximately 60-90 minutes. It was found that acceptance and commitment therapy successfully increased self-esteem scores and decreased fear of being single in single adult women. Acceptance and commitment therapy helped participants to accept and embrace their condition, provided a ‘locker’ for negative experiences and emotions, fought cognitive distortions, and facilitated participants to find their principles and goals in life.